#### Answer

x=-$\frac{4}{9}$

#### Work Step by Step

-2(x+3.5)+4(2x-1)=7x-5(2x+3)
-2x-7+8x-4=7x-10x-15
6x-11=-3x-15
9x=-4
x=-$\frac{4}{9}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

x=-$\frac{4}{9}$

-2(x+3.5)+4(2x-1)=7x-5(2x+3)
-2x-7+8x-4=7x-10x-15
6x-11=-3x-15
9x=-4
x=-$\frac{4}{9}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.